Evolution of residual stress, microstructure and cyclic performance of the equiatomic high-entropy alloy CoCrFeMnNi after deep rolling. (December 2021) - Oevermann, T.; Wegener, T.; Liehr, A.; Hübner, L.; Niendorf, T.
Highlights: Deep rolling (DR) leads to increased YS, UTS and an increased hardness. Compressive residual stresses are induced with a maximum of −850 MPa after DR. Twin bands evolve in the near surface area after DR at cryogenic temperature. Fatigue properties can be improved by means of DR between 10 3 and 10 6 cycles. S-N curves (initial state vs. DR) reveal a point of intersection for Nf > 10 6 . Abstract: High-cycle fatigue tests were performed on differently deep rolled conditions of the equiatomic high-entropy alloy (HEA) CoCrFeMnNi. Twinning in the near-surface layer of specimens deep rolled at cryogenic temperature is revealed by electron-backscatter diffraction. As internal failure mode and similar fatigue lives are found irrespective of the deep rolling temperature, these twins are not expected to significantly contribute to the fatigue properties of the surface treated HEA. S-N curves of the initial state and deep rolled conditions revealed a point of intersection at low stress amplitudes. This unexpected behaviour is explained based on the interplay of several characteristics of the near-surface layers.